On the δ-chromatic numbers of the Cartesian products of graphs - Tangjai Wipawee; Pho-on Witsarut; Vichitkunakorn Panupong (Open Mathematics)
In this work, we study the δδ -chromatic number of a graph, which is the chromatic number of the δδ -complement of a graph. We give a structure of the δδ -complements and sharp bounds on the δδ -chromatic numbers of the Cartesian products of graphs. Furthermore, we compute the δδ -chromatic numbers of various classes of Cartesian product graphs, including the Cartesian products among cycles, paths, and stars.